Simple Authentication Scheme for Personal Digital Assistants using the Hidden Markov Model ToolKit - Ching, Ho Chiung; Eswaran, Chikkannan (2007)
Personal Digital Assistants (PDA) are becoming increasingly important as a business tool. A modern day PDA is loaded with various business application ranging from office related software (word processors, spreadsheets & presentation software), personal information manager (organizers, contact information managers, calendars) as well as communication software(web browsers, email clients, instant messaging software). These applications facilitate the management, transformation and presentation of information even as the user is constantly on the move. A PDA is also used to store confidential information that is vital for a business' competitiveness. At the same time, a PDA's small size and ability to connect to remote devices and services (Internet in this case) allows it to be carried with a person constantly. This combination of practical utility, business information confidentiality and mobility unfortunately makes the PDA a target of theft or being more prone to being misplaced As such, it is of vital importance that a PDA is secured from unauthorized access. This paper will present a simple authentication scheme for a PDA based on the Hidden Markov Model Toolkit (HTK). In this scheme, authentication is done on the user's uttered speech in combination with a known password. The speech signal is recognized using HTK and compared to the known password.